A Highly Sensitive Electrochemical Sensor of Polysulfides in Polymer Lithium-Sulfur Batteries. Issue 8 (5th May 2020) - Meddings, Nina; Judez, Xabier; Li, Chunmei; Garcia-Araez, Nuria
Abstract : A novel and highly sensitive electrochemical sensor is used here to detect polysulfides as intermediates formed during cycling of a solid polymer lithium-sulfur cell. The formation of polysulfides is found to produce dramatic changes in the shape and magnitude of the voltammetric current of the sensor. Impedance analysis is also applied to quantify electrochemical properties such as charge-transfer and Warburg resistances of the polysulfide species. This new experimental set-up enables a rigorous analysis of the electrochemical properties of polysulfides and sulfur species, and it is used here to elucidate the fundamental cause of the effect of the choice of lithium salt (LiTFSI or LiFSI) on solid polymer Li-S cell performance.